Information System Of Student Point Violations (Case Study Of Sma Muhammadiyah 7 Serbelawan) - Mhd Zhasnitra Arrafiq; Arie Rafika Dewi; Husni Lubis (Penerbit Jurnal Indonesia, 2023)
Efforts to strengthen school discipline can be done in various ways. For example, at the middle school level, points for violations committed by students are calculated based on the rules set by the school. The number of fault points counted varies from warning to calling the parent at the highest level, and notifying the maximum number of fault points to the parent. SMA Muhammadiyah 7 serbelawan has issued a code of conduct. The school will apply penalty points for all infractions committed by students in an attempt to enforce disciplinary action. To improve teacher performance in dealing with problem students, the authors designed a system for calculating student violation points using the oriented objects technology method. By using the object oriented technology method, it will build a system systematically and regularly in order to achieve a goal based on the abstraction of existing objects and the presence of this system will certainly greatly help teacher performance, especially counseling guidance teachers and counseling guidance teachers, problems in recapitulating all student violations that occur in Muhammadiyah 7 Serbelawan High School. With a system that has been computerized and integrated with databases, it will be able to facilitate the process of finding student data that violates and conducting counseling easily and documents are stored neatly in the database.